Spaces of memory and memories of space in Alaa al-Aswany's The Yacoubian Building and Elif Shafak's The Flea Palace - TURAN, AYŞEGÜL (Springer, Van Godewıjckstraat 30, 3311 GZ Dodredht, Netherlands, 2019)
Alaa al-Aswany's The Yacoubian Building and Elif Shafak's The Flea Palace emerge as microcosmic representations of contemporary Egypt and Turkey, respectively, through their focus on apartment buildings and their residents. Both the Yacoubian Building of Cairo and Bonbon Palace of Istanbul, once famous for their grandeur and now in a dilapidated state, embody the social, political and economic transformation of each society not only through the depiction of diverse characters inhabiting these buildings but also with the architectural and spatial characteristics of the buildings themselves. As social hierarchies and relations are mapped onto spatial organization and architectural details, the very physicality of these buildings gains importance to comprehend the complicated, and at times tumultuous, individual and collective stories and histories. This article focuses on the uses of space and history of urban space to examine the representation of the notions of memory, nostalgia, and disillusionment within the context of these two societies. As these multi-story buildings become manifestations of the multilayered history and structure of each society, they also reveal the tensions and fragmentation in contemporary urban life and space. While both these novels, with the microcosm of buildings' residents, strive to create a sense of collective belonging as one big family living under the same roof, their rather bleak portrayals of the buildings, nonetheless, underline a fragmented and ruptured sense of belonging and overall disenchantment, thus questioning the idea of shared destiny and the promise of common future.
Keywords: Space; Memory; Cultural Memory; Social Transformation; Nation